Uncoupled vibrations in functionally graded Timoshenko beam - Huyen, Nguyen Ngoc; Khiem, Nguyen Tien (Vietnam Journal of Science and Technology, 2016)
Free vibration of FGM Timoshenko beam is investigated on the base of the power law distribution of FGM. Taking into account the actual position of neutral plane enables to obtain general condition for uncoupling of axial and flexural vibrations in FGM beam. This condition defines a class of functionally graded beams for which axial and flexural vibrations are completely uncoupled likely to the homogeneous beams. Natural frequencies and mode shapes of uncoupled flexural vibration of beams from the class are examined in dependence on material parameters and slendernes